(untitled) (Al-Qamar, 2021)
This investigation intends to discuss the need and importance of dams, its construction related issues and its history in Islamic perspective. As, water is the greatest blessing of Allah Almighty and human life mostly depends on water more than food. In view of the importance of water, every civilization or human and animal population has preferred to live on the banks of rivers and streams. Because of this importance of water, man started to store water since ancient times. In modern times, especially industrial and scientific development has greatly increased the needs and use of water. That is why water is called Blue Gold and every developed country in the world wants to store water in large quantities. In this article, the construction of dams, the difference between dams and barrages, history of dams, dams in the era of Prophethood, dams built in Caliphate, has been conferred. In this context, the situation of dams in Pakistan, the projects of dam construction, the costs incurred on these projects and other issues have been elaborated briefly.